Political elites and state repression in Turkmenistan - Pedro Luis Rubio Terés (Comillas Journal of International Relations, 2017)
The aim of the article is to analyze the power relations among the Turkmen political elites so as to grasp a better understanding of the rationale of constraint and its supremacy over all features of society. Through the recent history of domination, the burden of foreign financial dependence, and the ancestral configuration of the society; the reader will be able to perceive how life lingers under an imposed ‘objective order’ of things which renders all counteraction utopian. That is, a complete immersion into the logics of repression of this enigmatic Central Asian republic.